Women and microcredit in rural agrarian households of Uganda: Match or mismatch between lender and borrower? - Namayengo, Faith; van Ophem , Johan A.C.; Antonides, Gerrit (Applied Studies in Agribusiness and Commerce, 2016)
The alignment of microfinance programs with the context and expectations of the recipients is critical for ensuring clients’ satisfaction and desired program outcomes. This study sought to investigate the extent to which the objectives and design of the BRAC microfinance program match the expectations, context and characteristics of female borrowers in a rural agrarian setting in Uganda. Quantitative and qualitative methods were used to obtain socio-demographic, personality and microenterprise (ME) characteristics of existing borrowers, incoming borrowers and non-borrowers and to obtain information about the microcredit program. We found that BRAC uses a modified Grameen group-lending model to provide small, high-interest rate production loans and follows a rigorous loan processing and recovery procedure. BRAC clients are mainly poor subsistence farmers who derive income from diverse farming and non-farm activities. The major objective to borrow is to meet lump-sum monetary needs usually for school fees and for investment in informal small non-farm businesses. Many borrowers use diverse sources of funds to meet repayment obligations. Defaulting on loans is quite low. The stress caused by weekly loan repayment and resolution of lump-sum cash needs were identified as reasons for women to stop borrowing. The limited loan amounts, the diversions of loans to non-production activities, the stages of the businesses and the weekly recovery program without a grace period may limit the contribution of these loans to ME expansion and increase in income.